Influence and the Control of Shield Tunneling on Ancient Tower Vibration - Xu Liang; Jian Xu; Yapeng Zhang; Xinquan Gao; Xuetao Zhou; Zonghao Yuan; Min Zhang; Jian Wu; Long Liu (Advances in Civil Engineering)
In recent years, to effectively mitigate the issue of urban traffic congestion, tunnels have become widely used new type of road. However, when the soil layer is excavated and disturbed, the resulting vibration affects the safety of the buildings above it, especially for ancient buildings that are very sensitive to vibrations. Taking the White Tower in Hangzhou as an example, in this paper, the vibration response propagation of large-diameter shield tunnel excavation to adjacent ancient towers is studied through field measurements. The vibration response of the unexcavated south line tunnel is predicted by using 3D numerical analysis software, and the optimal construction parameters are obtained. The study found that the frequency domain component of the White Tower bedrock vibration caused by shield tunneling is mainly 5–20 Hz, and the vibration response attenuates significantly beyond 40 m. Further, reducing the propulsive force can reduce the vibration response of the White Tower; therefore, controlling the propulsion and reducing the tunneling velocity can reduce the vibration response.